BLOCK GAMES GROUP PEMANFAATAN BLOCK GAMES GROUP TERHADAP PERKEMBANGAN ANAK USIA 5 TAHUN DI TK HELLO KIDS KEC. PANCUR BATU TAHUN 2022 - Juliana Munthe; Edy Marjuang; Ribur Sinaga; Heny Rista; Astaria Ginting; Elsa Dela Vista Marbun (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Social interaction needs to be developed from an early age because it affects the next child's life. One of the efforts so that children can learn to interact socially is at school, teachers must realize how important social interaction is for children, through education children will be easier to reach with the surrounding environment. Lack of social development of children can cause children not to have readiness in socializing with their peers caused by shyness in speaking so that children prefer to be alone or prefer to go with their parents wherever they go instead of having to play together. her friend. To solve this problem, the author implemented a game idea called “Block Games Group”. This game is done by forming mini teams (small groups) in order to create cooperation between teams that can hone children's abilities. The method used in this activity consists of 3 stages, namely preparation, implementation and evaluation, starting with forming "One Small Groups" consisting of 5 children and measuring children's development with KPSPS before and after using Block Games Group, so that children's development can be seen. well. From the activities carried out, all participants attended, of which 30 participants registered in this activity, it was found that as many as 23 participants (77%) children with appropriate development and 7 participants (23%) with doubtful development